Norovirus outbreaks due to contaminated drinking water and probable person-to-person transmission, Kerala, India, 2021 - Amjith Rajeevan; Manikandanesan Sakthivel; Nikhilesh Menon; Sachin KC; Harisree Sudersanan; Ramya Nagarajan; Mohankumar Raju; Sharan Murali; Chethrapilly Purushothaman Girish Kumar; Anukumar Balakrishnan; Renuka Raveendran; Dineesh Perumbil; et al. (Elsevier, 2024)
Background: In July 2021, the Alappuzha district in Kerala, India, reported an unexpected number of acute gastroenteritis (772) cases (Outbreak A). On October 10, 2021, a university in Wayanad, Kerala, reported 25 acute gastroenteritis cases (Outbreak B). We described both the outbreaks and determined the agent, source and risk factors. Methods: We defined a suspected case as the occurrence of vomiting or at least three episodes of loose stools within 24 h and a confirmed case as those with stool samples/rectal swabs positive for norovirus. We did a matched case-control study in Outbreak A and a retrospective cohort study in Outbreak B. We calculated the adjusted odds ratio (aOR) in outbreak A, relative risk (aRR) in outbreak B and population attributable fraction (PAF). We tested stool and water samples for bacteria and viruses. Results: We identified Group II norovirus in stool samples in both outbreaks and 4/5 water samples in Outbreak A. Suspected norovirus infection was associated with drinking inadequately boiled water from the municipal water supply in outbreak A [aOR: 4.5; 95 % C.I: 1.2-15.8; PAF: 0.23] and well water in hostels in outbreak B [aRR: 2.2; 95 % C.I: 1.2-3.9; PAF: 0.15]. In Outbreak A, groundwater from tube wells was mixed in the municipal water supply overhead tanks without chlorination. Conclusion: The gastroenteritis outbreaks were caused by Group II norovirus due to the consumption of inadequately boiled contaminated groundwater (outbreak A) and well water (outbreak B). We recommended superchlorination of overhead tanks and wells and boiled water for drinking.